Phylloporia lespedezae sp. nov. (Hymenochaetaceae, Basidiomycota) from China - Ren, Guang-Juan; Wu, Fang (Phytotaxa, 2017)
A new species, Phylloporia lespedezae, is described from Shanxi Province on the basis of morphological, ecological characters and molecular evidence. It is characterized by having an annual, pileate basidiocarps with wavy edge, duplex context separated by a black line, a monomitic hyphal system with simple septate generative hyphae, the presence of fusoid cystidioles, yellowish, broadly ellipsoid, thick-walled basidiospores, and growing on Lespedeza (Fabaceae) only. Phylogenetic analysis based on nuclear large subunit ribosomal DNA (nLSU) strongly support P. lespedezae as a distinct species within the genus of Phylloporia. Detailed description with illustration is provided for the new species and its relationships with similar species are discussed. In addition, a key to all 41 species of Phylloporia is provided.